1998
DOI: 10.1021/bi980502d
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Quantum Yield of Primary Radical Pair Formation in Photosystem II by Site-Directed Mutagenesis Affecting Radical Cations and Anions

Abstract: Pigment-protein interactions play a significant role in determining the properties of photosynthetic complexes. Site-directed mutants of Synechocystis PCC 6803 have been prepared which modify the redox potential of the primary radical pair anion and cation. In one set of mutants, the environment of P680, the primary electron donor of Photosystem II, has been modified by altering the residue at D1-His198. It has been proposed that this residue is an axial ligand to the magnesium cation. In the other set, the D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 29 publications
4
84
2
Order By: Relevance
“…The differences between the in vivo and in vitro measurements may be a consequence of the loss of the Mn cluster which is known to influence the rate of reduction of P + by Y Z (82,91) and the difference in reduction potential between Y Z •/Y Z and P + /P (92). The differences with the results of Merry et al (43) may be due to their use of reaction center preparations as well as the early times at which their measurements are made (60 ps) as compared to our own which are on the seconds time scale. The slower measurements here allow ample time for protein-based relaxations to occur.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The differences between the in vivo and in vitro measurements may be a consequence of the loss of the Mn cluster which is known to influence the rate of reduction of P + by Y Z (82,91) and the difference in reduction potential between Y Z •/Y Z and P + /P (92). The differences with the results of Merry et al (43) may be due to their use of reaction center preparations as well as the early times at which their measurements are made (60 ps) as compared to our own which are on the seconds time scale. The slower measurements here allow ample time for protein-based relaxations to occur.…”
Section: Discussioncontrasting
confidence: 78%
“…This possibility has been previously proposed by Rutherford and co-workers (32,109) and by Dekker and van Grondelle (33). From the results of Merry et al (43) it is clear that mutations that affect the reduction potentials P A + / P A and the Pheo -/Pheo also have an impact on the yield of charge separation at 60 ps following the excitation pulse. Thus radical pair states that include P A + and Pheo -(mostly P A + Pheo -) are already present at this time and are in equilibrium with the excited state of the reaction center.…”
Section: Location Of 3 P As a Function Of Temperaturementioning
confidence: 51%
See 1 more Smart Citation
“…The E m (P680/P680 ϩ ) value was estimated to be less positive than ϩ1,210 mV. The E m (Phe a/Phe a Ϫ ) value for the PS II complexes from T. elongatus WT*, where only the psbA 3 gene expressed, was Ϫ505 mV, whereas a site-directed mutagenesis study with Synechocystis PCC 6803 (56) showed that substitution of Glu at position 130 of D1 with Gln decreased the free energy difference ⌬G CS , corresponding to a shift in the E m (Phe a/Phe a Ϫ ) value by ϩ33 mV. Such a mutational effect on the energetics was also confirmed by thermoluminescence measurements (57).…”
Section: Discussionmentioning
confidence: 93%
“…The importance of H-bonds to cofactors in the bacterial RC has been well studied (13). As shown previously in the case of Photosystem II (14), the loss of such a H-bond should shift the Chl's reduction potential to more negative values, thus altering the rate, and possibly the yield, of ET to the targeted ec3 Chl.…”
mentioning
confidence: 91%